2019
DOI: 10.7759/cureus.6432
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Myofibroblastic Tumor of the Lung: An Extremely Rare Condition in Adults

Abstract: Inflammatory myofibroblastic tumors (IMTs) of the lung were first reported in 1939. The most common site of predilection is the lungs of the pediatric population. They are extremely rare in adults, constituting less than 1% of adult lung tumors. They are mesenchymal neoplasms that may arise in the soft tissues of almost every organ. IMTs often arise from excessive inflammatory response, and as the name implies, they are composed of myofibroblastic spindle cells accompanied by an inflammatory infiltrate of plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…Though IMT are considered as benign entity, however, malignant transformation has also been reported in the literature including recurrence and rarely metastatic disease. 12 Patients usually present with diversity of symptoms ranging from being asymptomatic and discovered incidentally 13 to various symptoms such as cough, chest pain, shortness of breath, hemoptysis, fever and fatigue, with manifestations depending on the size and location of the tumor. 14 Our patient presented with symptoms of pain and shortness of breath.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though IMT are considered as benign entity, however, malignant transformation has also been reported in the literature including recurrence and rarely metastatic disease. 12 Patients usually present with diversity of symptoms ranging from being asymptomatic and discovered incidentally 13 to various symptoms such as cough, chest pain, shortness of breath, hemoptysis, fever and fatigue, with manifestations depending on the size and location of the tumor. 14 Our patient presented with symptoms of pain and shortness of breath.…”
Section: Discussionmentioning
confidence: 99%
“…They constitute less than 1% of adult lung tumours. 1 The tumour usually occurs in paediatric population and young adults. 2 Inflammatory myofibroblastic tumour is also known as inflammatory pseudotumour or plasma cell granuloma.It is usually classified as a benign tumour.…”
Section: Introductionmentioning
confidence: 99%
“…An IMT is a mesenchymal neoplasm of intermediate malignancy (rarely metastasizing) according to the 2013 World Health Organization classification [1], which may develop in almost every organ [2]. Some authors reported that an IMT in the lung is rare, with an incidence of 0.04% [3] to 0.3% [4].…”
Section: Discussionmentioning
confidence: 99%
“…(1) Esses tumores são mais frequentes em crianças e adultos jovens, representando cerca de 50% de todas as neoplasias pulmonares em lactentes e menos de 1% dos tumores pulmonares em adultos. (3) Devido ao amplo espectro de manifestações radiológicas e comportamento clínico inespecífico, esses tumores são difíceis de diagnosticar. A ressecção cirúrgica geralmente é realizada em lesões solitárias para estabelecer o diagnóstico e fornecer tratamento adequado.…”
Section: Ao Editorunclassified